Relationship between attachment styles and nomophobia in medical students: A cross-sectional study - Omid Ebrahimi; Delaram Mohammadi (Research and Development in Medical Education)
Background: Nomophobia, despite being a relatively new phenomenon, has had significant and wide-ranging impacts on various life aspects and the physical and mental health of individuals, particularly the younger generation. This study sought to explore the correlation between attachment styles and nomophobia among students. Methods: This study employed a descriptive-cross-sectional design to examine the relationships between variables using the correlation method. A sample of 245 students was selected from the medical student population in Tabriz, Iran, using a convenience sampling method in October 2023. The participants filled out questionnaires on nomophobia and attachment styles. The collected data were analyzed using the Pearson correlation statistical method in SPSS26. Results: The mean (±SD) scores of nomophobia were (males: 7.52±3.04, females: 74.93±3.77), attachment avoidance (males=20.37±3.72, females=19.03±2.98), anxious attachment (males: 7.52±3.04, females: 74.93±3.77) and secure attachment (males: 20.97±4.93, females: 22.35±5.07). The correlation results between the variables showed a positive and significant relationship between anxious attachment and nomophobia (P<0.001; r=0.543) and between avoidant attachment and nomophobia (P<0.01; r=0.322). There was also a significant negative relationship between secure attachment and nomophobia (P<0.001; r=0.475). Conclusion: The findings suggest that insecure attachment contributes to problematic smartphone use and nomophobia, whereas individuals with secure attachment can control addictive smartphone behaviors. Therefore, attachment styles have a significant impact on nomophobia.